The Development of Guidelines on Promoting Bicycle Use for Tourism in Khao Yai National Park - D. Watthanaklang; V. Ratanavaraha (International Association of Lowland Technology, 2019)
At present, bicycle use for both health and tourism is supported but it is found that most Thai people do not popularly use bicycles. This study aimed to seek for the factors promoting Thai people to use bicycles by choosing KhaoYai National Park, where there are a large number of tourists, to be studied with the application of the Theory of planned behavior-TPB. The factors, which were considered, included Attitude, Subjective norm, Perceived behavioral control, and Additional factors which were the factor of infrastructure, and number of bicycle possession in the family. The data used in this study were 429 Thai tourists. The data analysis was done by using Structural Equation Modeling. From data analysis, it was found that Perceived behavioral control, Subjective norm, and Attitude influenced behavioral intention in bicycle use at statistical significance 0.01. For Infrastructure, and number of bicycle possession in the family, they positively influenced behavioral intention in bicycle use in KhaoYai National Park at statistical insignificance. This study can be used as guidelines for the government or involved organizations to determine the pertinent policies on promoting bicycle use.